Real‐world data on safety and efficacy of venetoclax‐based regimens in relapsed/refractory t(11;14) multiple myeloma. (3rd February 2020) - Basali, Diana; Chakraborty, Rajshekhar; Rybicki, Lisa; Rosko, Nathaniel; Reed, Janice; Karam, Maryann; Schlueter, Kristen; Dysert, Hayley; Kalaycio, Matt; Valent, Jason
Summary: The treatment for relapsed/refractory multiple myeloma (RRMM) continues to be challenging despite recent therapeutic advancements. Venetoclax, an inhibitor of the anti‐apoptotic protein BCL‐2, is a promising agent, especially in patients harbouring t(11;14). Our objective was to review our experience with venetoclax‐based regimens at our institution. All ten RRMM patients treated with venetoclax were included and had a median of six prior lines of therapy. The overall response rate was 78% and one patient with cardiac amyloidosis and MM achieved a cardiac organ response. Haematologic toxicities requiring red blood cell and platelet transfusion and non‐haematologic toxicities, most commonly gastrointestinal upset, were observed.